A leucine zipper pair-based lipid vesicle for image-guided therapy in breast cancer. Issue 13 (11th January 2016) - Lim, Eun-Kyung; Bae, Panki; Kim, Haeran; Jung, Juyeon
Abstract : We developed a controllable image-guided therapy system as a powerful tool for diagnostic and therapeutic applications. Abstract : We developed a controllable image-guided therapy system as a powerful tool for diagnostic and therapeutic applications. The system uses a two-step pretargeting approach that takes advantage of the highly selective binding interactions between leucine zipper pairs. It consists of the utilization of a tumor pretargeting probe for diagnosis and, if necessary, a probe for therapy.